2016
DOI: 10.1016/j.jpeds.2016.05.070
|View full text |Cite
|
Sign up to set email alerts
|

Growth Outcomes of Preterm Infants Exposed to Different Oxygen Saturation Target Ranges from Birth

Abstract: Objective To test whether infants randomized to a lower oxygen saturation (SpO2) target range while on supplemental oxygen from birth will have better growth velocity from birth to 36 weeks postmenstrual age (PMA), and less growth failure at 36 weeks PMA and 18–22 months corrected age. Study design We evaluated a subgroup of 810 preterm infants from the Surfactant, Positive Pressure, and Oxygenation Randomized Trial, randomized at birth to lower (85–89%, n=402, GA 26 ± 1wk, BW 839 ± 186 g) or higher (91–95%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…It is most likely due to differences in energy and protein supply during the first postnatal weeks, and it stands to reason that early exclusive enteral feeding results in considerably higher macronutrient supply in this time period. This hypothesis is supported by a recent report on nutritional intakes in extremely premature infants5 where a mean total energy intake of 100 kcal/kg/day was not achieved until postnatal day 28.…”
Section: Discussionsupporting
confidence: 57%
“…It is most likely due to differences in energy and protein supply during the first postnatal weeks, and it stands to reason that early exclusive enteral feeding results in considerably higher macronutrient supply in this time period. This hypothesis is supported by a recent report on nutritional intakes in extremely premature infants5 where a mean total energy intake of 100 kcal/kg/day was not achieved until postnatal day 28.…”
Section: Discussionsupporting
confidence: 57%
“…32,33 Thus it is not surprising that growth and neurodevelopmental outcomes were not as good as outcomes reported for less selected groups of premature infants. 34,35 For those concerned about the systemic effects of bevacizumab on premature infants, this study should provide some reassurance that the adverse effects of bevacizumab reported in the previous large observational study were not apparent in our randomized infants.…”
Section: Discussionmentioning
confidence: 64%
“…However, having this type of control has not led to significant reductions in postnatal growth failure at 36 weeks of postmenstrual age (PMA). Postnatal growth failure (weight < 10 th percentile) occurs in up to 60% ( 1 3 ) of the nearly 80,000 infants born preterm at 32 weeks of gestation or less every year in the United States ( 4 ).…”
Section: Introductionmentioning
confidence: 99%